Tobacco use among drivers and conductors in Western Uttar Pradesh, India - Parashari, Aditya; Ahmad, Shahid; Asthana, Smita; Saxena, Saumya (Indian Journal of Community Health, 2017)
Background: Tobacco use is the leading global cause of preventable death. There is estimation that three quarters of these deaths will be in low and middle income countries. Very few studies were available on the tobacco habit of transport staff from India. Aims and Objectives: Prevalence of habits for various tobacco products and initiating/ quitting patterns of these habits in Drivers and conductors. Material and Methods: Cross sectional survey was conducted on the staff of drivers conductors, technicians of government bus depot. Out of total 903 staff 702 could be contacted and surveyed. Results: The mean age was 36.4 ± 10.3 years. The mean age of initiation was 10-15 years. This have very high rate (77.9%) of tobacco and alcohol use. As a single habit chewing was more popular compared to smoking followed by alcohol. More than half of the chewers consume more than 4 pkts (20-25 grams in weight) of Gutka per day an even 30 to 40 pkts of Gutka consumption in a single day was reported by some staff. Addiction was a common feature for tobacco habit in this community for tobacco use (97%). Peer group pressure was the most important single cause of initiation of tobacco habits. Nearly half (44.3%) tobacco users want to quit the habit. Most common symptoms which tobacco users have were burning sensation in stomach or acidity. Conclusions: Repeated awareness programmes about the ill effect of tobacco and counselling/ de-addiction programmes are very much needed from the transport department and government are needed to improve the situation